Synthesis of Derivatives of 3-Phenyl-2H-Pyrano[2,3-b] Quinoline-2-Ones and Comparison of Their Biological Activities - VENKATESH KUMAR, N.; RAJENDRAN, S.P. (Asian Journal of Chemistry, 2010)
Synthesis of a series of title compounds including several hitherto unknown derivatives of 3-phenyl-2H-pyrano (2,3-b) quinoline- 2-ones (3) is reported by the Perkin type reaction of 3-formyl-2-quinolones (2) with sodium salt of phenylacetic acid, The 3-formyl-2-quinolones inturn were obtained from 2-chloro-3- formylquinolines (1). Structures of all the products have been established by spectral and elemental analysis data. Biocidial activities have been tested in vitro.